Compensation of Voltage disturbances in hybrid AC/DC Microgrids using series converter - Dehnavi, Saeed Daneshvar; Shayani, Ehsan (Ciência e Natura, 2015)
In this paper a series power electronic converter is proposed to improve power quality of AC/DC hybrid microgrids. An injection transformer which is series with AC microgrid is used beside the series converter to inject voltage for the purpose of voltage disturbances compensation. The series converter by using a simple and effective control system in stationary reference framework of d-q-0 is proposed to compensate voltage sag and swell, source unbalanced voltages, voltage harmonics of the utility. In these types of micrigrids a lot of voltage disturbances have occurred due to large number of converters. Moreover, it is not required to use a storage energy system like battery; the required power is supplied by DC microgird, so the proposed system is very efficient. Simulation results in the MATLAB/Simulink environment have verified the appropriate performance of the proposed method.